Amorphous Calcium Phosphate Formation and Aggregation Process Revealed by Light Scattering Techniques - Vida Čadež; Ina Erceg; Atiđa Selmani; Darija Domazet Jurašin; Suzana Šegota; Daniel M. Lyons; Damir Kralj; Maja Dutour Sikirić (Crystals, 2018)
Amorphous calcium phosphate (ACP) attracts attention as a precursor of crystalline calcium phosphates (CaPs) formation in vitro and in vivo as well as due to its excellent biological properties. Its formation can be considered to be an aggregation process. Although aggregation of ACP is of interest for both gaining a fundamental understanding of biominerals formation and in the synthesis of novel materials, it has still not been investigated in detail. In this work, the ACP aggregation was followed by two widely applied techniques suitable for following nanoparticles aggregation in general: dynamic light scattering (DLS) and laser diffraction (LD). In addition, the ACP formation was followed by potentiometric measurements and formed precipitates were characterized by Fourier transform infrared spectroscopy (FTIR), powder X-ray diffraction (PXRD), transmission electron microscopy (TEM), and atomic force microscopy (AFM). The results showed that aggregation of ACP particles is a process which from the earliest stages simultaneously takes place at wide length scales, from nanometers to micrometers, leading to a highly polydisperse precipitation system, with polydispersity and vol. % of larger aggregates increasing with concentration. Obtained results provide insight into developing a way of regulating ACP and consequently CaP formation by controlling aggregation on the scale of interest.